Cross-Situational Word Learning in Two Foreign Languages: Effects of Native Language and Perceptual Difficulty - Tuninetti, Alba; Mulak, Karen E.; Escudero, Paola (Frontiers in Communication, 2020)
Cross-situational word learning (CSWL) paradigms have gained traction in recent years as a way to examine implicit statistical learning in infancy, childhood, and adulthood. However, no study thus far has examined how CSWL paradigms may provide viable learning pathways for second language (L2) word learning. Here, we used a CSWL paradigm to examine how native Australian English (AusE) speakers learned novel Dutch (Experiment 1) and Brazilian Portuguese (Experiment 2) word-object pairings. During each learning phase trial, two words and objects were presented without indication as to which auditory word belonged to which visual referent. The two auditory words formed a non-minimal or vowel minimal pair. Minimal pairs were classified as ‘perceptually easy’ or ‘perceptually difficult’ based on the acoustic-phonetic relationship between AusE and each L2. At test, participants again saw two visual referents but heard one auditory label and were asked to select the corresponding referent. We predicted that accuracy would be highest for non-minimal pair trials (in which the auditory words associated with the target and distractor object formed a non-minimal pair), followed by perceptually easy minimal pairs, with lowest accuracy for perceptually difficult minimal pair trials. Our results support these hypotheses: While accuracy was above chance for all pair types, in both experiments accuracy was highest for non-minimal pair trials, followed by perceptually easy and then perceptually difficult minimal pair trials. These results are the first to demonstrate the effectiveness of CSWL in adult L2 word learning. Furthermore, the difference between perceptually easy and perceptually difficult minimal pairs in both language groups suggests that the acoustic-phonetic relationship between the L1-L2 is an important factor in novel L2 word learning in ambiguous learning scenarios. We discuss the implications of our findings for L2 acquisition, cross-situational learning and encoding of phonetic detail in a foreign language.